Medication non-adherence and associated factors among older adult stroke survivors in China - Cao, Wenjing; Kadir, Azidah Abdul; Wang, Juan; Hu, Lin; Wen, Linlan; Yu, Mei; Peng, Liqun; Chen, Lanying; Luo, Na; Hassan, Intan Idiana (Frontiers in Pharmacology, 2022)
Aims Medication non-adherence has remained a common and costly global health issue of growing importance among older adults. This study aims to determine the prevalence of and associated factors related to medication non-adherence among older adult stroke survivors in China. Methods and results In this cross-sectional study, a total of 402 older adult stroke survivors were recruited from three tertiary hospitals in China. The results of the survey showed that 61.4% exhibited medication non-adherence. The chances of medication non-adherence among older adult stroke survivors who had primary school or less educational levels was higher than among those who had senior secondary and junior college educational levels [OR (95%CI) = 0.440(0.249，0.778)] as well as those who had a bachelor’s degree or above educational levels [OR (95%CI) = 0.367(0.202，0.667)]. Moreover, the probability of medication non-adherence with 4~5 and ≥6 types of total prescription medications per day increased by 1.993 times [OR (95%CI) = 1.993(1.190，3.339))] and 2.233 times [OR (95%CI) = 2.233(1.159，4.300)], respectively, as compared to when there were ≤3 types. Furthermore, medication non-adherence decreased with the increase in health literacy scores (β = -0.641, (95% CI; (0.913, 0.965)) and BMQ Specific-Necessity scores (β = -0.131, (95% CI; 0.806, 0.995)). On the other hand, when the BMQ specific-concerns score increased by one unit, medication non-adherence increased by 11.1% [OR (95%CI) = 1.111(1.044, 1.182)]. Conclusion The present study found that patient medication adherence among older adult stroke survivors in China is problematic and associated with educational levels, total prescribed drugs per day, beliefs about medication, and health literacy scores. This indicates that measures should be taken to enhance medication adherence among such higher-risk populations.